How proposing an activity to a person with an intellectual disability can imply a limited identity - Antaki, Charles and Walton, Chris and Finlay, W.M.L. (Discourse & Society, 2007)
In residential homes for people with learning or intellectual disabilities (or mental retardation, in North American usage), a routine way for staff members to structure residents' time is to propose outside activities (e.g. shopping trips to town, attendance at a concert and so on). We identify one common way of proposing such activities that reveals a subtle but significant aspect of the staff's understanding of the residents' identities. Staff often introduce an activity not by mentioning its actual qualities (e.g. `Do you want to go and see a church concert with lots of singing?'), but by associating it with a given individual (e.g. `Do you want to go to a concert with Bill?'). This practice favours the social aspect of the residents' choices over any other, and encourages the residents' conceptions of themselves as people with feelings who care about others, and who are, in turn, cared about. We discuss the implications of such an apparently positive identity ascription.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTA3MDc1NDcz